Proses Penulisan Katalog Skripsi Mahasiswa dengan Menggunakan Microsoft Access di Perpustakaan Universitas Bung Hatta Padang - Veradia, Osdeka; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This paper describes the process of catalog penuliasan student thesis by using Microsof Access at Bung Hatta University Library Padang. This study aimed to describe the process of cataloging and Industrial Engineering student thesis by using Microsof Access 2010 at the Bung Hatta University Library Padang. Data were collected through observation and direct observation during fieldwork prektek at Bung Hatta University Library Padang. Analyzing data descriptively. By analyzing the data, writing the catalog summed up as follows. 1) The process of making catalogs: a) call namber, b) the title of the thesis, c) description of the author, d) tension edition, e) imprensum, f) a physical description of the thesis or collation, 2) Making use of Microsof Student Thesis Catalog acces 2010. Keywords: microsoft access; library